Place in Entrepreneurial Storytelling: A Study of Cultural Entrepreneurship in a Deprived Context - Kimmitt, Jonathan (Wiley-Blackwell Publishing Ltd., 2025)
We extend the cultural entrepreneurship perspective by investigating how entrepreneurs in deprived contexts gain legitimacy by leveraging proprietary and public places in their entrepreneurial storytelling. Inspired by the sociology of place, we present a longitudinal study of ten new venture journeys over four years in Kasoa, Ghana. We identify three distinct ways places are used in entrepreneurial narratives: projective significance of place, connective significance of place, and authoritative significance of place. We show how impoverished entrepreneurs construct and communicate places in diverse ways, not only as locations, but also as material and symbolic resources that provide legitimacy for their venturing activities. Drawing from our findings, we generate a model of place-based cultural entrepreneurship and elaborate place as a central resource in cultural entrepreneurship and new venture creation in deprived contexts.